The Effects of special Exercises in developing some of mechanical changes for close runand rising up and the high jump achievement according to Fosbory Flop method - Khaled, Waled; Hussein, Wesam (Journal of Physical Education, 2014)
The aim of this research is to know some values of the mechanical changes of the study sample by using some changes of world champions asacritiria. Then set special exercises according to movement analyses to the high jump and know the effect of the special exercises on developing some mechanical changes in high jump. The research is done on a sample of two Iraqi champions in high jump who are chosen typically. The special exercises took ( 10 ) ten weeks , about three courses weekly and ( 50 – 90 ) minutes for each course . A program and competitions were used in the special providing period and in two methods : periodical training of high stress and repeated training. When the program period was finished, the distance test was done and it treated citation by using the citation case (SPSS )The special exercises achieved positively significant effect in all mechanical changes and achieve in high jump. The writer of this research advised to take care in the special exercises and choose it and if they are suitable to the fouls they aim to correct. Also it is important to give it enough time in training courses .